2011
DOI: 10.1063/1.3658865
|View full text |Cite
|
Sign up to set email alerts
|

Dirac spinors in Bianchi-I f(R)-cosmology with torsion

Abstract: We study Dirac spinors in Bianchi type-I cosmological models, within the framework of torsional $f(R)$-gravity. We find four types of results: the resulting dynamic behavior of the universe depends on the particular choice of function $f(R)$; some $f(R)$ models do not isotropize and have no Einstein limit, so that they have no physical significance, whereas for other $f(R)$ models isotropization and Einsteinization occur, and so they are physically acceptable, suggesting that phenomenological arguments may sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 25 publications
5
60
0
Order By: Relevance
“…In many recent works, it has been shown that the spinor field possesses non-diagonal components of the energy momentum tensor [7,35]. The main question arises that what is the reason for non-triviality of non-diagonal components of the energy-momentum tensor?…”
Section: The Spinor Inflationary Model Of Universe In Super String Thmentioning
confidence: 99%
“…In many recent works, it has been shown that the spinor field possesses non-diagonal components of the energy momentum tensor [7,35]. The main question arises that what is the reason for non-triviality of non-diagonal components of the energy-momentum tensor?…”
Section: The Spinor Inflationary Model Of Universe In Super String Thmentioning
confidence: 99%
“…generalizing the usual relations that hold in a Zeld'ovich universe. The Jacobs parametrisation, given by the first equation in (26), still holds although with a time dependent δ = √ Ω Σ . From the definition (30), the time-dependent quasi-Kasner exponents satisfy the differential equatioṅ…”
Section: A Definition Of Quasi-kasner Exponentsmentioning
confidence: 99%
“…Regarding type-6 spinors, still J = 0 and K = 0, however, the flag S is zero, terming it a dipole spinor field. Flagdipole spinor fields were shown to be a legitimate solution of the Dirac field equation in a torsional setup [6][7][8], whereas Elko and Majorana uncharged spinor fields represent type-5 spinors, although a recent example of a charged flag-pole spinor has been shown to be a solution of the Dirac equation [9]. More physical important examples on the Lounesto classification can be found in Refs.…”
Section: General Bilinear Covariants and Spinor Field Classesmentioning
confidence: 99%